Presenteísmo, carga de trabalho coletiva e desempenho funcional em trabalhadores da saúde - Vieira, Elamara Marama de Araujo (2019)
Workforce must be an item of ongoing concern in health services, and it has to be understood which way the conditions whereby the work is performed reflects on workers’ functionality in different levels of attention and complexity, it becomes imperative the delineation of actions and strategies. Objectives: To identify whether the collective workload is a resource for maintenance of functional performance in presenteeism professionals from health public sector, considering the modulating effect of the attention level whereby professionals practice their activities. Method: It is a cross-sectional study held in 24 health services of municipal network in João Pessoa/Paraíba (basic and specialized levels). By stratified probabilistic sampling, 323 workers of direct assistance to the user were approached. Data were collected through specific questionnaires and analyzed by means of five phases (factor analyses, cluster analysis, weight of evidence, MANOVA, and correspondence analysis). Results: Data enabled to form 3 groups of analysis from the setting of musculoskeletal symptoms related to complaints of presence and intensity of pain in regions of skeleton axial, such as cervical, thoracic, and lumbar. Analysis showed that high collective workload have been associated to low performance in presenteeism professionals by musculoskeletal symptoms, which may identify that the workload in team can be used as a resource to maintain the performance. However, it could not be clearly established if these relations are distinct by the level of health care in which the professional practices its functions. Conclusions: Regulations developed by members of a team in working environments may cushion the impact of presenteeism over performance. Therefore, in situations which there are sick professionals is necessary to find ways to lead an efficient team work to maintain the performance of all workers in the best level possible.